2017
DOI: 10.1111/mec.14449
|View full text |Cite
|
Sign up to set email alerts
|

Context‐dependent vertical transmission shapes strong endosymbiont community structure in the pea aphid, Acyrthosiphon pisum

Abstract: Animal-associated microbiomes are often comprised of structured, multispecies communities, with particular microbes showing trends of co-occurrence or exclusion. Such structure suggests variable community stability, or variable costs and benefits-possibilities with implications for symbiont-driven host adaptation. In this study, we performed systematic screening for maternally transmitted, facultative endosymbionts of the pea aphid, Acyrthosiphon pisum. Sampling across six locales, with up to 5 years of collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
106
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(113 citation statements)
references
References 119 publications
(217 reference statements)
6
106
1
Order By: Relevance
“…McLean et al () found stable coinfections to be possible between multiple combinations of different aphid symbionts and even between multiple strains of the same symbiont, H. defensa . Similarly, in a long‐term study of aphid symbiont communities, Rock et al () found that the bacteria Serratia symbiotica and Rickettsiella viridis co‐occurred more often than expected, a phenomenon that was explained by their ability to promote each other's transmission to the next host generation. Wolbachia is also positively associated with Spiroplasma within Drosophila neotestacea (Fromont, Adair, & Douglas, ).…”
Section: Insect‐associated Symbiotic Bacteriamentioning
confidence: 96%
“…McLean et al () found stable coinfections to be possible between multiple combinations of different aphid symbionts and even between multiple strains of the same symbiont, H. defensa . Similarly, in a long‐term study of aphid symbiont communities, Rock et al () found that the bacteria Serratia symbiotica and Rickettsiella viridis co‐occurred more often than expected, a phenomenon that was explained by their ability to promote each other's transmission to the next host generation. Wolbachia is also positively associated with Spiroplasma within Drosophila neotestacea (Fromont, Adair, & Douglas, ).…”
Section: Insect‐associated Symbiotic Bacteriamentioning
confidence: 96%
“…Ne F , effective female population size; M T , maternal transmission rate; H T , horizontal transmission rate. The blue square highlights the range of parameters values that is likely to include the symbionts of D. neotestacea while the dotted purple one is likely to include those of the pea aphid (Chen & Purcell, ; Moran & Dunbar, ; Peccoud et al, ; Rock et al, ). (c) Example of simulation where drift created a strong positive association.…”
Section: Introductionmentioning
confidence: 99%
“…The second section featured a number of manuscripts that investigated the structure of the microbiome in an attempt to understand the drivers of microbiota community assembly and turnover. Some contributions weighed in on the role of host phylogeny vs. ecology (Erlandson, Savage, Wei, Cavender‐Bares, & Peay, ; Ivens, Gadau, Kiers, & Kronauer, 2018; Hernandez‐Gomez, Briggler, & Williams, ; Kohl, Dearing, & Bordenstein, ; Nishida & Ochman, ; Roth‐Schulze et al., ; Schuelke, Pereira, Hardy, & Bik, ), others probed how the presence of hosts themselves alters the microbiota around them (Chen & Parfrey, ; Shukla, Vogel, Heckel, Vilcinskas, & Kaltenpoth, ), one investigated patterns of co‐infection (Rock et al, ) and one documented changes in microbiota during development (Prest, Kimball, Kueneman, & McKenzie, ). A few studies in this section studied the structure of the microbiome with manipulative experiments (e.g., Chen & Parfrey, ; Erlandson et al, ; Morella, Gomez, Wang, Leung, & Koskella, ; Raymann, Bobay, & Moran, ).…”
Section: Special Issuesmentioning
confidence: 99%